Intracochlear Pressures in Simulated Otitis Media With Effusion: A Temporal Bone Study. Issue 7 (August 2018) - Alhussaini, Mohamed A.; Banakis Hartl, Renee M.; Benichoux, Victor; Tollin, Daniel J.; Jenkins, Herman A.; Greene, Nathaniel T.
Abstract : Hypothesis: Simulated otitis media with effusion reduces intracochlear pressures comparable to umbo velocity. Background: Otitis media with effusion is a common cause of temporary hearing loss, particularly in children, producing deficits of 30 to 40 dB. Previous studies measured the effects of simulated effusion on ossicular mechanics; however, no studies have measured cochlear stimulation directly. Here, we compare pressures in the scala vestibuli and tympani to umbo velocity, before and after induction of simulated effusion in cadaveric human specimens. Methods: Eight cadaveric, hemi-cephalic human heads were prepared with complete mastoidectomies. Intracochlear pressures were measured with fiber optic pressure probes, and umbo velocity measured via laser Doppler vibrometry (LDV). Stimuli were pure tones (0.1–14 kHz) presented in the ear canal via a custom speculum sealed with a glass cover slip. Effusion was simulated by filling the mastoid cavity and middle ear space with water. Results: Acoustic stimulation with middle ear effusion resulted in decreased umbo velocity up to ∼26 dB, whereas differential pressure ( P Diff ) at the base of the cochlea decreased by only ∼16 dB. Conclusion: Simulating effusion leads to a frequency-dependent reduction in intracochlear sound pressure levels consistent with audiological presentation and prior reports. Results reveal that intracochlear pressure measurements ( P SV and P ST ) decrease less than expected, and less than the decrease in P Diff . The observed decrease in umbo velocity is greater than in the differential intracochlear pressures, suggesting that umbo velocity overestimates the induced conductive hearing loss. These results suggest that an alternate sound conduction pathway transmits sound to the inner ear during effusion.